Degradation of organophosphorus flame retardant tri(chloro-propyl)phosphate (TCPP) by (001) crystal plane of TiO2 photocatalysts. Issue 10 (29th April 2021) - He, Huan; Wang, Xiaohan; Cheng, Chen; Yang, Shaogui; Wang, Xiaomen; Liu, Qing; Wang, Yong; Wang, Zunyao; Zhang, Limin; Sun, Cheng
ABSTRACT: This paper demonstrates the successful synthesis of TiO2 with (001) crystal plane; its morphology and structure were characterized using XRD, TEM and Raman spectrometer. The results showed that TiO2 nanosheets were bounded by (001) facets on both the top and bottom. TiO2 -001/UV photocatalytic process was proved to be a powerful method for degrading tri(chloro-propyl) phosphate (TCPP) in aqueous solution. Under the given parameters, 95% of TCPP was removed in 360 min. The photodegradation followed the pseudo-first-order kinetic reaction. The reactive species during photocatalytic oxidation of TiO2 -001 was mainly hydroxyl radical. TCPP was decomposed into small molecule organics by hydroxyl radicals, along with the release of PO 4 3 − and Cl −, and most of these intermediates were eventually degraded into carbon dioxide and water. GRAPHICAL ABSTRACT: